Effect of Stiffeners on the Axial Strength of Face-to-Face Unequal-Angle Cold-Formed Steel Columns - Beulah Gnana Ananthi Gurupatham; Krishanu Roy; James Boon Piang Lim (Buildings)
Cold-formed steel (CFS) unsymmetrical angles are increasingly used in structural applications such as portal frames, roof trusses, and transmission towers. However, research on built-up face-to-face unsymmetrical CFS angle columns (FFUACs) with stiffeners remains limited. This study addresses this gap by presenting the findings from six experimental investigations on intermediate FFUACs connected using intermittent screw fasteners. The results offer insights into failure deformation patterns and load-axial shortening behaviour. A nonlinear finite element (FE) model was developed to account for material and geometric nonlinearity, with experimental results used for validation. This study contributes 166 new data points, including six experimental tests under concentric compression and 160 finite element analysis (FEA) results focused on the compressive strength of FFUACs. Additionally, this study evaluates the performance of existing design guidelines based on the direct strength method (DSM). The DSM strength predictions were found to be less conservative for stub FFUAC specimens that failed due to local buckling and more conservative for short FFUAC specimens that failed due to a combination of local and flexural buckling. A revised DSM methodology is proposed to address these discrepancies.